2010
DOI: 10.1002/ange.200907039
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling a Chemically Enhanced Photoswitch: Bridged Azobenzene

Abstract: The possibility to reversibly photoisomerize azobenzene (AB) has made it one of the most ubiquitous light-sensitive molecular switches. [1][2][3][4][5][6][7][8][9][10] Opto-and nanomechanical devices [9,10] that convert light to mechanical action, for instance, exploit the considerable stretching of AB on Z!E isomerization. In biochemical studies, AB has been integrated into synthetic peptides and foldamers to photocontrol their conformational dynamics. [6,11] Photoaddressable materials such as image-storage m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 25 publications
4
27
0
1
Order By: Relevance
“…In our surface hopping AIMD simulation 47 at the state-averaged CASSCF (SA-CASSCF) level, it was shown that cis to trans isomerization in nπ * excitation occurs via two-step rotation mechanism, accompanying rotations of the central NN part and two phenyl rings, and this process can be classified into two types with respect to the orientation of the rotation, namely, clockwise and counterclockwise rotation pathways; the calculated quantum yields and lifetime in the excited states are in very good agreement with the corresponding experimental results. 47 The similar reaction mechanism was also reported in the dynamics simulations by Doltsinis et al 45,49,50 and Thiel et al 55 As described above, the transient Raman spectra indicate that the NN stretching frequency of trans-azobenzene is almost unchanged (decreases by only 12 cm −1 ) in the S 1 (nπ * ) state. 12 There are several theoretical reports on vibrational frequencies for trans-azobenzene in the ground state at the MP2, density functional theory (DFT), and CASSCF levels, 20,21,23,25,30 while, to our knowledge, there is only one report on frequencies of trans-azobenzene in the S 1 (nπ * ) state, which employed the CASSCF method.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our surface hopping AIMD simulation 47 at the state-averaged CASSCF (SA-CASSCF) level, it was shown that cis to trans isomerization in nπ * excitation occurs via two-step rotation mechanism, accompanying rotations of the central NN part and two phenyl rings, and this process can be classified into two types with respect to the orientation of the rotation, namely, clockwise and counterclockwise rotation pathways; the calculated quantum yields and lifetime in the excited states are in very good agreement with the corresponding experimental results. 47 The similar reaction mechanism was also reported in the dynamics simulations by Doltsinis et al 45,49,50 and Thiel et al 55 As described above, the transient Raman spectra indicate that the NN stretching frequency of trans-azobenzene is almost unchanged (decreases by only 12 cm −1 ) in the S 1 (nπ * ) state. 12 There are several theoretical reports on vibrational frequencies for trans-azobenzene in the ground state at the MP2, density functional theory (DFT), and CASSCF levels, 20,21,23,25,30 while, to our knowledge, there is only one report on frequencies of trans-azobenzene in the S 1 (nπ * ) state, which employed the CASSCF method.…”
Section: Introductionsupporting
confidence: 76%
“…27,28,30,31,42,58 On-the-fly dynamics simulations were also performed for the photoisomerization of azobenzene on the basis of semiempirical molecular orbital calculations with the surface hopping method 29,33,55,59,61 and with the multiple spawning method. 32 Recently, ab initio molecular dynamics (AIMD) simulations at the CASSCF level 26,47,54,57 and Car-Parrinello molecular dynamics simulations 34,45,49,50 were also performed for the photoisomerization of azobenzene in nπ * excitation. In our surface hopping AIMD simulation 47 at the state-averaged CASSCF (SA-CASSCF) level, it was shown that cis to trans isomerization in nπ * excitation occurs via two-step rotation mechanism, accompanying rotations of the central NN part and two phenyl rings, and this process can be classified into two types with respect to the orientation of the rotation, namely, clockwise and counterclockwise rotation pathways; the calculated quantum yields and lifetime in the excited states are in very good agreement with the corresponding experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The S 1 state decay time result comes close to the experiment time scales of about 50 fs by Siewertsen and co-workers [25,26]. The ultrafast excited state decays are also observed in other theoretical studies with different methods [17,28,[30][31][32]66]. Fig.…”
Section: à6supporting
confidence: 88%
“…For the excited state, the SCC-DFTB approach is extended to the time-dependent case with the timedependent density functional linear response theory [11]. Azobenzene and its derivatives have received considerable attention experimentally and theoretically during the past three decades, due to their potential applications in molecular switches, molecular motors, optical information storage and processing devices [12][13][14][15][16][17][18][19][20][21][22][23][24]. The pioneering studies of the photochromic properties of bridged-azobenzene (abbreviated as Br-AB and shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although the basis for these dynamical simulations was set early in the 1970s, [2,3] only in the last fifteen years, [4][5][6][7][8] with the development of computational capabilities and efficient quantum chemical methods, have they become a routine tool for research in photochemistry and photophysics. [9][10][11] Much of the research in nonadiabatic dynamics simulations has focused on the relaxation processes following photoexcitation of organic molecules. [1,12,13] These simulations have provided a mechanistic view of ultrafast processes by determining the relative importance and time constants for each available reaction pathway.…”
Section: Introductionmentioning
confidence: 99%